Effective removal of high-chroma rhodamine B over Sn0.215In0.38S/reduced graphene oxide composite : synergistic factors and mechanism of adsorption enrichment and visible photocatalytic degradation - Wu, Zhibin (2020)
The highly visible light active Sn0.215In0.38S/reduced graphene oxide (SIS/RGO) composites with hierarchical porous were prepared by a facil solvothermal in-situ growth method for rhodamine B (RhB) removal coupling adsorption with photocatalysis. The morphology, composition and photocurrent response of the adsorptive photocatalysts were systematically characterized. The investigation results showed that both adsorption and photocatalytic processes were affected by pH, ionic strength and so on. The RhB adsorption process complied with pseudo-second order kinetics equation and Langmuir isotherm model, and the SIS/RGO-2.5% showed the optimum adsorption-photocatalytic performance. The maximum adsorption capacity of SIS/RGO-2.5% was 173.97 mg·g−1 mainly attributing to the electrostatic attraction, π − π interaction and surface complexation. Due to efficient mass transfer efficiency, dye self-sensitization and effective transfer of photogenerated carriers, the photodegradation efficiency of RhB over SIS/RGO-2.5% was as high as 96.25% under visible light irradiation for 25 min and the corresponding reaction rate constant is 3.98 times of Sn0.215In0.38S. The results of free radical capture and electron spin resonance experiments indicated that the [rad]O2− and h+ were the main active species attacking RhB. Furthermore, cyclic experiments showed the considerable reusability and stability of photocatalysts for the RhB degradation.